Pharmacist Provision of Hormonal Contraception in the Oregon Medicaid Population. Issue 6 (June 2019) - Anderson, Lorinda; Hartung, Daniel M.; Middleton, Luke; Rodriguez, Maria I.
Abstract : OBJECTIVE: To describe early utilization of pharmacist prescription of contraception in Oregon's Medicaid program. METHODS: Using Oregon Medicaid claims data, we conducted a retrospective analysis and quantified overall and monthly trends in pharmacist-prescribed contraceptives from January 1, 2016, to December 31, 2017. Our population was restricted to patients obtaining a new prescription for oral and transdermal methods and who had continuous Medicaid coverage during the study period. We summarized demographic and utilization characteristics, including whether patients were continuing or switching methods or initiating contraception. New prescriptions were those written to patients who did not have one for hormonal contraception in the prior 30 days. To assess program safety, we examined rates of prescriptions to patients with medical contraindications to contraceptive use. RESULTS: Among the 3, 614 patients receiving a new prescription for oral or transdermal contraceptives in the Oregon Medicaid program from all health care providers, 367 (10%) received their prescription from a pharmacist. Five months after implementation, pharmacists filled an average of 61 prescriptions per month as the prescriber. Most claims originated from retail chain pharmacies (94%) in urban locations (71%). The majority of patients who were prescribed contraception by pharmacists (73.8%) had no history of contraceptive prescriptions in the preceding 30 days (n=252). Ages ranged from 13 to 49 years, fewer patients lived in a rural location (35.7%), most received a combined hormonal pill (90.5%), and the average day's supply dispensed was 65 (range of 21–364 days). Fewer than 5% (12) of patients had a diagnostic code indicating a possible contraindicating comorbidity. CONCLUSION: Among Medicaid enrollees, we found that 10% of all new oral and transdermal contraceptive prescriptions were written by pharmacists. Abstract : Among Oregon Medicaid enrollees, 10% of all new oral and transdermal contraceptive prescriptions were written by pharmacists.